Usefulness of retinal optical coherence tomography angiography evolution in cases of systemic diseases - Rakusiewicz, Klaudia; Kanigowska, Krystyna; Hautz, Wojciech; Ziółkowska, Lidia (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Assessment of retinal blood vessels in ophthalmoscopy fundus examination is a basic and standard exam in case of systemic diseases such as: diabetes mellitus, hypertension, arteriosclerosis and kidney disease. The introduction of retinal optical coherence tomography angiography (OCTA) enables the imaging of small retinal blood vessels in a highly precise and repeatable manner providing high resolution images. This review presents the changes in retinal blood vessels in the course of systemic disease based on optical coherence tomography angiography and the clinical application of this method. In the future, OCTA, as an accurate, routine and non-invasive method, may become commonly used not only in ophthalmology but also in other fields of medicine such as diabetology, hypertensiology, cardiology, rheumatology, pediatrics and others.